Determining Factors of Digital Public Service Management Implementation Policy at Subdistrict Level in South Jakarta City - Marthalina, Marthalina; Dione, Frans; Saribulan, Nur (Universitas Padjadjaran, 2025)
This research examined the determining factors in implementing digital public service policies at the sub-district level in South Jakarta, focusing on policy substance, task behavior of implementers, work network interactions, target group participation, and resources as proposed by Hamdi (2014). Digital public services at the sub-district level are aligned with the Electronic Based Government System (SPBE) framework but still face various challenges. This research adopts a post-positivist approach using qualitative data collection methods. The novelty of this study remained in its emphasis on the determining factors influencing the success of digital public service policies at the sub-district level. The findings revealed that determining factors influence the implementing of digital transformation policies in public services at the sub-district level in South Jakarta. Clear policies accommodated to local needs, cross-agency collaboration, and improvement of public digital literacy, socio-cultural influences, and the importance of participatory approaches involving community feedback are identified as supporting factors for the success of digital public services at the sub-district level.